ANALYSIS OF MARKETING STRATEGIES IN INCREASING SALES TURNOVER IN TOY ENTREPRENEURS AT SUZUYA TANJUNG MORAWA - Taufik Hidayat; Nuri Aslami (Journal of Social Research, 2022)
This study aims to analyze the marketing strategy at the Toy Stand, especially the marketing mix at Suzuya Tanjung Morawa. This study uses a qualitative method, namely a case study that produces descriptive data as outlined in words. Data collection techniques in this study the authors made a direct visit to the children's toy booth to conduct personal interviews with the owner of the toy stand, namely Mr. Ricky Gunawan equipped with sales data. The results showed that the strategy in increasing sales turnover of Toy Stands, namely the segmentation, targeting, positioning strategies and especially the marketing mix had been implemented well although not fully implemented. To be able to further increase sales turnover at the Toy stand at Suzuya Tanjung Morawa, the company should be able to innovate the products sold by the Toy Booth owner, expand the sales market, add promotional activities, expand the trend of today's children's toys and increase creativity in layout. how to set up the Stand so that it can produce more revenue from sales